FOREIGN EXPERIENCES OF USING DECORATIVE PLANTS IN THE INTERIORS OF PUBLIC BUILDINGS - Abdullayev Allayor Mamadiyor o’g’li; Xatamboyeva Umida Farxod qizi (Journals Park Publishing, 2022)
The article mentions brief recommendations about the main principles of using decorative plants in the interior environment. This article gives recommendations on the cultivation of plants used in residential areas and the use of ornamental plants in the greening of residential houses, work buildings, streets, and recreation areas. Even decorating the interiors of houses and buildings with plants has become a tradition since time immemorial, today it is considered a new field to turn the interior environment into a comfortable space for people with the participation of decorative plants, based on the laws of the interior and landscape, and the most urgent goals of floristry.
Keywords: декоративный, интерьер, фитодизайн, общественное, помещение, флора, архитектурная композиция.